A DISTRIBUTION AND AN IDENTIFICATION OF Culicoides SPECIES (Diptera: Ceratopogonidae) IN BOGOR - Ana Sahara; Malole Malole; Koesharto Koesharto; Sendow Sendow; Sukarsih Sukarsih (Jurnal Sain Veteriner, 2000)
A distribution and an identification of Culicoides species collected around the cattle farm have been investigated. The purpose of the research is to know the distribution and the species of Culicoides that might be a relevance to bluetongue virus tranmission. A number of 2117Culicoides (Diptera. Ceratopogonedae) was collected from around the castle farm in Depok dan Cibungbulang Bogor municipality. The collection was carried out by pirbright type miniatur light trap. The identification of species of Culicoides was based on the morphological character of the insect according to Wirth and Hubert. The result showed that the number of Culicoides was found in Depok region more than in Cibungbulang. There were 14 species identified from the two region. In Depok, the specieses of Culicoides were dominated by C. parahumeralis Wirth & Hubert, C. actoni Smith, C. oxystoma KiefFer and C. peregrinus Kiefier; whereas in Cibungbulang, they were dominated by C. parahumeralis, C. orientalis Macfiei, C. peregrinus and C oxystoma. The species suspected in their role of bluetongue transmission are C. actoni, C. peregrinus, C.oxystoma and C. orientalis.